DSM-IV made easy the clinician's guide to diagnosis - Morrison, James R. 1940- (Guilford Press, 1995)
DSM-IV presents a challenging task for all clinicians. Just reviewing these diagnostic standards is time consuming and often confusing even to the most experienced practitioner, but learning the standards alone does not immediately translate into clinical application. This book helps professionals quickly learn how to apply the new criteria to patients. Every DSM-IV diagnosis is simplified and clearly interpreted, emphasizing what a clinician needs to know most when making a diagnosis. Case vignettes, extensive evaluations, and the author's informed commentary combine to enable mental health practitioners to readily incorporate DSM-IV into practice